Enhanced Anticarcinogenic and Antimicrobial Response of Synthesized Tungsten Oxide Nanoparticles (Journal of Scientific Research, 2023)
In the present study, we fabricated tungsten trioxide nanoparticles (WO3 NPs) from a tungsten complex [W(C13H10NO)3] of ligand N-salicylideneaniline with tungstic acid as the precursor. Nanoparticles were synthesized using the direct thermal decomposition method. These nanoparticles were evaluated for cytotoxicity influence on human breast cancer MCF7 cell line (adenocarcinoma). The observed results suggested that WO3 can destroy 50 % of viable cells after 24 h of incubation at 37 °C. Based on these results, we concluded that WO3 nanoparticles could be a potential drug carrier candidate against human breast cancer cells based on the amount of the drug. In addition, WO3 nanoparticles exhibited significant antimicrobial and antifungal activity.